Predicting the risk for aberrant opioid use behavior in patients receiving outpatient supportive care consultation at a comprehensive cancer center - Yennurajalingam, Sriram; Edwards, Tonya; Arthur, Joseph A.; Lu, Zhanni; Najera, John; Nguyen, Kristy; Manju, Joy; Kuriakose, Leela; Wu, Jimin; Liu, Diane; Williams, Janet L.; Reddy, Suresh K.; et al. (Cancer, 2018)
BACKGROUND Opioid misuse is a growing crisis. Patients with cancer who are at risk of aberrant drug behaviors are frequently underdiagnosed. The primary objective of this study was to determine the frequency and factors predicting a risk for aberrant opioid and drug use behaviors (ADB) among patients who received an outpatient supportive care consultation at a comprehensive cancer center. In addition, the screening performance of the Cut Down‐Annoyed‐Guilty‐Eye Opener (CAGE) questionnaire adapted to include drug use (CAGE‐AID) was compared with that of the 14‐item Screener and Opioid Assessment for Patients With Pain (SOAPP‐14) tool as instruments for identifying patients at risk for ADB. METHODS In total, 751 consecutive patients with cancer who were referred to a supportive care clinic were reviewed. Patients were eligible if they had diagnosis of cancer and had received opioids for pain for at least 1 week. All patients were assessed using the Edmonton Symptom Assessment Scale (ESAS), the SOAPP‐14, and the CAGE‐AID. SOAPP scores ≥7 (SOAPP‐positive) were used to identify patients who were at risk of ADB. RESULTS Among the 729 of 751 (97%) evaluable consults, 143 (19.6%) were SOAPP‐positive, and 73 (10.5%) were CAGE‐AID–positive. Multivariate analysis revealed that the odds ratio of a positive SOAPP score was 2.3 for patients who had positive CAGE‐AID scores (P < .0001), 2.08 for men (P = .0013), 1.10 per point for ESAS pain (P = .014), 1.13 per point for ESAS anxiety (P = .0015), and 1.09 per point for ESAS financial distress (P = .012). A CAGE‐AID cutoff score of 1 in 4 had 43.3% sensitivity and 90.93% specificity for screening patients with a high risk of ADB. CONCLUSIONS The current results indicate a high frequency of an elevated risk of ADB among patients with cancer. Men and patients who have anxiety, financial distress, and a prior history of alcoholism/illicit drug use are at increased risk of ADB. In this study, the authors found a high frequency of cancer patients with elevated risk of aberrant opioid and drug behavior. Male patients and those with anxiety, financial distress, and prior alcoholism/illicit drug use are at increased risk of aberrant opioid and drug behavior.